1976
DOI: 10.1029/ja081i007p01369
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the spectra of geomagnetic variations having periods from 5 min to 4 hours

Abstract: The geomagnetic field variation spectra for the period range of 5 min to 4 hours were analyzed at 64 world observatories to discover systematic behavior in the spectral composition that could be associated with the time of day, season, solar cycle, activity level, component direction, and geographical location of the station. There was found no consistent frequency location for peaks in the spectral composition. Rather, the displays of spectral amplitudes A were mostly ‘linear’ in form, often obeying A ∼ Tm, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
1

Year Published

1976
1976
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 69 publications
7
26
1
Order By: Relevance
“…This study complements an earlier publication (CAMPBELL, 1976) which focused upon the monthly average spectral characteristics.…”
Section: Introductionsupporting
confidence: 55%
“…This study complements an earlier publication (CAMPBELL, 1976) which focused upon the monthly average spectral characteristics.…”
Section: Introductionsupporting
confidence: 55%
“…[46] Our suggested magnetic field power law exponent of 1.8 is within the range of 1.0-4.0 found by Campbell [1976] though somewhat smaller than the other studies listed in Table 1. With the exception of the Buchert et al [1999] study, all the listed studies use reasonable amounts of data and there are no particular aspects of their methodology which would give us reason to expect different exponents.…”
Section: Comparison With Previous Studiesmentioning
confidence: 53%
“…The results of these studies are summarized in Table 1. In the largest such study, using 123 data years from 64 geomagnetic observatories over a wide range of latitudes and longitudes, Campbell [1976] concluded that the power spectra from individual observatories in the period range from 5 min to 4 hours (0.07 -3.3 mHz) were mostly power law in form with an exponent range 1 a 4.0, but usually a % 2.0, and that no consistent frequency location for spectral peaks was observed.…”
Section: Introductionmentioning
confidence: 99%
“…One purpose of the investigation is to determine the predictable characteristics of field levels on undisturbed days in order to evaluate the limitations of accuracy obtainable in magnetic mapping, to improve the selection of favorable times for survey observations, to adjust various field measurements to more reproducible baselines, and to find the modifications of the measurements by the induced fields. The studies started at the short period end of the spectra at 0.3 sec (WERTZ and CAMPBELL, 1976) and have already extended to field variations with periods of 4 hr (CAMPBELL, 1976(CAMPBELL, a, b, 1977. Before investigating the solar-quiet (Sq) diurnal and semidiurnal variations (24-and 12-hr periods) it was necessary to extract the lunar contributions to the semidiurnal field changes.…”
Section: Discussionmentioning
confidence: 99%